Stability of -Jordan Homomorphisms from a Normed Algebra to a Banach Algebra - Yang-Hi Lee (Abstract and Applied Analysis)
We establish the hyperstability of -Jordan homomorphisms from a normed algebra to a Banach algebra, and also we show that an -Jordan homomorphism between two commutative Banach algebras is an -ring homomorphism.